Development of Small-Molecule Fluorescent Probes Targeting Enzymes - Yuan-Xiang Li; Dong-Tai Xie; Ya-Xi Yang; Zhao Chen; Wu-Yingzheng Guo; Wen-Chao Yang (Molecules, 2022)
As biological catalysts, enzymes are vital in controlling numerous metabolic reactions. The regulation of enzymes in living cells and the amount present are indicators of the metabolic status of cell, whether in normal condition or disease. The small-molecule fluorescent probes are of interest because of their high sensitivity and selectivity, as well as their potential for automated detection. Fluorescent probes have been useful in targeting particular enzymes of interest such as proteases and caspases. However, it is difficult to develop an ideal fluorescent probe for versatile purposes. In the future, the design and synthesis of enzyme-targeting fluorescent probes will focus more on improving the selectivity, sensitivity, penetration ability and to couple the fluorescent probes with other available imaging molecules/technologies.